2022
DOI: 10.1111/bcp.15536
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative impact of pre‐analytical process on plasma uracil when testing for dihydropyrimidine dehydrogenase deficiency

Abstract: Aims Determining dihydropyrimidine dehydrogenase (DPD) activity by measuring patient's uracil (U) plasma concentration is mandatory before fluoropyrimidine (FP) administration in France. In this study, we aimed to refine the pre‐analytical recommendations for determining U and dihydrouracil (UH2) concentrations, as they are essential in reliable DPD‐deficiency testing. Methods U and UH2 concentrations were collected from 14 hospital laboratories. Stability in whole blood and plasma after centrifugation, the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In view of the predominant hepatic expression of DPD, such an impact of cytolysis on uracilemia is not surprising and could contribute, at least partially, to the observed intra-individual variability of uracilemia. 14,15 Concerning the influence of sex, the interpretation of our results appears to be more complicated. Indeed, being male was identified as an independent factor of increased uracilemia (in accordance with the results of a previous study 26 ), whereas patients with U ≥ 16 μg/L in the absence of a DPYD variant were more often female.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In view of the predominant hepatic expression of DPD, such an impact of cytolysis on uracilemia is not surprising and could contribute, at least partially, to the observed intra-individual variability of uracilemia. 14,15 Concerning the influence of sex, the interpretation of our results appears to be more complicated. Indeed, being male was identified as an independent factor of increased uracilemia (in accordance with the results of a previous study 26 ), whereas patients with U ≥ 16 μg/L in the absence of a DPYD variant were more often female.…”
Section: Discussionmentioning
confidence: 81%
“…13 In France, health authorities recommend DPD deficiency screening by measuring uracilemia, with thresholds of 16 and 150 μg/L for partial and complete DPD deficiency, respectively. 5 Additional studies are urgently needed to validate these questionable thresholds and define dose reduction according to uracilemia, as well as to better characterize the variability of uracilemia 14,15 and its determinants. In addition to preanalytical conditions, 15 uracilemia varies according to the circadian rhythm of DPD 16 and nutritional status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no consensus for the maximum time of blood storage and several studies have demonstrated consistent increases in uracil concentrations when whole blood is stored at room temperature before centrifugation. [2][3][4] More specifically, average uracil concentrations were found to be increased by 27% after 1 hour, 2 21% after 1.5 hours, 3 and ~25% after 2 hours. 4 Our unpublished data shows an increase of 12.7% after 2 hours in whole blood and at room temperature.…”
mentioning
confidence: 94%
“…The Netherlands; 2 Department of Clinical Chemistry, Erasmus Medical Center, Rotterdam, The Netherlands; 3…”
mentioning
confidence: 99%